Dispersing Perylene Diimide/SWCNT Hybrids: Structural Insights at the Molecular Level and Fabricating Advanced Materials - Tsarfati, Yael; Strauß, Volker; Kuhri, Susanne; Krieg, Elisha; Weissman, Haim; Shimoni, Eyal; Baram, Jonathan; Guldi, Dirk Michael; Rybtchinski, Boris (Journal of the American Chemical Society, 2015)
The unique properties of carbon nanotubes (CNT) are advantageous for emerging applications. Yet, the CNT insolubility hampers their potential. Approaches based on covalent and noncovalent methodologies have been tested to realize stable dispersions of CNTs. Noncovalent approaches are of particular interest as they preserve the CNTs structures and properties. We report on hybrids, in which perylene diimide (PDI) amphiphiles are noncovalently immobilized onto single wall carbon nanotubes (SWCNT). The resulting hybrids were dispersed and exfoliated both in water and organic solvents in the presence of two different PDI derivatives, PP2b and PP3a. The dispersions were investigated using cryogenic transmission electron microscopy (cryo-TEM), providing unique structural insights into the exfoliation. A helical arrangement of PP2b assemblies on SWCNTs dominates in aqueous dispersions, while a single layer of PP2b and PP3a was found on SWCNTs in organic dispersions. The dispersions were probed by steady-state and time-resolved spectroscopies, revealing appreciable charge redistribution in the ground state, and an efficient electron transfer from SWCNTs to PDIs in the excited state. We also fabricated hybrid materials from the PP2b/SWCNT dispersions. A supramolecular membrane was prepared from aqueous dispersions and used for size-selective separation of gold nanoparticles. Hybrid buckypaper films were prepared from the organic dispersions. In the latter, high conductivity results from enhanced electronic communication and favorable morphology within the hybrid material. Our findings shed light onto SWCNT/dispersant molecular interactions, and introduce a versatile approach toward universal solution processing of SWCNT-based materials.
CRIS-Team Scopus Importer:2023-03-07